(untitled) (Italian Review of Legal History, 2023)
This article tends to trace in some European States (Switzerland, Estonia, Latvia and Lithuania) points in common related to direct democracy, some of which would be capable of bringing the electors back to voting. A derivation in this sense which appears clear is that between Switzerland, where direct democracy is strongly present, even to the point of being considered part of national identity, and the Baltic States, beginning in the period immediately following the First World War, when the Constitutions of the 1920’s were adopted. In that period, in which the newborn Baltic republics sought to provide themselves with democratic constitutions without any direct experience of their own, they were inspired on the one hand by the Constitution of Weimar of 1919 and on the other hand by Swiss direct democracy, well known also because many exiles from the central empires had lived in the little Alpine republic or, in any case, were aware of its particular institutions. At the base of democratization there were probably also some of the ideas of the French Revolution, which, beyond the constitutions of the revolutionary period which had enjoyed a very brief life, had been partially adopted by European constitutionalism. Thus, both the referendum, though often promoted from above, and the popular initiative as well as the recall (derived directly from the first ideas discussed in the French revolutionary period) not of single parliamentarians, but rather of the entire parliament as a whole, and in some cases of the head of State were introduced. In other cases, the body of the electorate was called upon to decide conflicts that might arise between the two highest organs, clearly not in imitation of the Swiss model, but rather of that of the Weimar Constitution. During the long period of incorporation in the U.S.S.R. (1940-1990), no authentic instrument of direct democracy was used, except for the recall, also of a single representative of the people, but entirely under the direction of the omnipresent and omnipotent Communist Party and thus far distant from a real intervention of the electorate body. This long period, however, did not eliminate national sentiment and the desire for independence; quite to the contrary, to demonstrate the illegitimacy of Soviet occupation, there was a wish to show the continuity with the period preceding the incorporation also from the constitutional and legislative points of view. Many of the institutions of the Constitutions of the 1920’s with regard to direct democracy survived in the constitutional provisions of the 1990’s, continuing the expression of the ideals linked to those alive and active in Switzerland. But, in conclusion to the reflections in these pages, one can note that the transfer of juridical institutions, all the more so at constitutional level, often leads to results which differ from the original model, because they are based on history, culture, political and social situations, which differ significantly from one another. The last, important question also remains open of whether direct democracy, especially where a high level of participation in voting or particular majorities are not required, is always compatible with the rights of minorities.